REVIEW OF PROMISING SOURCES OF UNCONVENTIONAL HYDROCARBONS IN THE FIELDS OF UKRAINE - Beizyk, O. S.; Vasko, A. I.; Kovbasyuk, I. M.; Charkovsky, V. M.; Kolisnyk, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Examples of alternative sources of raw materials are given, the features of the geological structure of typical sedimentary basins and deposits are described, possible depths of occurrence and physical and mechanical properties of hydrocarbon-bearing rocks are indicated. The conditions of formation and occurrence of unconventional types of hydrocarbons confined to various structures and formations are analyzed. The definitions of shale gas, shale oil, tight rock gas, coalbed methane, gas hydrates, oil sands, etc. are given. The factors influencing the choice of equipment and technology for oil and gas industry operations are given, taking into account the localization of deposits of each type of unconventional hydrocarbons. In particular, it is noted that the main ones are economic profitability and the cost of the extracted It is shown that today the most promising among all the listed types are shale gas and shale oil due to the fact that technologies for traditional oil and gas deposits can be used for their extraction. It is shown that coalbed methane is a promising associated mineral with significant reserves. An analysis of the conditions for the distribution of gas hydrate deposits in the Azov-Black Sea basin and the prospects for the oil and gas bearing capacity of impact structures in Ukraine is carried out. The issues of environmental protection and ensuring safe working conditions for personnel are briefly considered. The importance of unconventional types of hydrocarbons for increasing the mineral raw material base of the fuel and energy sector of the country is shown. The possibilities of biogas production and application from various sources, in particular organic waste and wastewater, are briefly analyzed.